The Implementation of Total Quality Management with Fishbone Method in PT. Kaliaren Jaya Plywood - Kriswanto, Kriswanto; Yusuf, Ayus Ahmad (Bina Bangsa International Journal of Business and Management, 2021)
The problem in this study is the Expansion of Total Quality Management with the Fishbone Method at PT. Kaliaren Jaya Plywood. Implementation of Total Quality Management by using the Fishbone method at PT. Kaliaren Jaya Plywood, obstacles faced in implementing Total Quality Management by using the Fishbone method at PT. Kaliaren Jaya Plywood, the efforts made in overcoming barriers in the Implementation of Total Quality Management by using the Fishbone method at PT. Kaliaren Jaya Plywood. The study results are: In the application of Total Quality Management using the Fishbone method at PT. Kaliaren Jaya Plywood has been very well such that production is the main thing in implementing company activities. Quality is the primary concern of both the product and its management. Continuous improvement to improve company performance. The obstacles encountered from the implementation of Total Quality Management by using the Fishbone method at PT. Kaliaren Jaya Plywood, namely: Lack of attention from production equipment which is still inadequate. Then the placement of production materials is still not following operational standards that have been previously determined. The effort felt by PT. Kaliaren Jaya Plywood is thought because the implementation of Total Quality Management is beneficial in the performance of company activities, especially for: Production must be further optimized so that the company becomes more advanced so that it can extend business cooperation with other companies. The company can optimize the performance of all departments to provide the best quality and increase the company's competitiveness. The research method used is qualitative. Whereby interviewing the president, director, head of the production, and employees. The research results using the fishbone method show that the implementation of total quality management is the main thing for companies and employees